Perspektif Hukum Pidana Terhadap Produk Belum Bersertifikat Halal dalam Usaha Perdagangan - Saraya, Sitta; Handayani, Yusrina; Ayu, Dian Ratu; Laksana, Andri Winjaya (Innovative: Journal Of Social Science Research, 2025)
The Indonesian state guarantees and protects all citizens in all aspects. Indonesian citizens have the right to legal protection, as stated in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, which states that “All citizens shall be equal before the law and government and shall uphold the law and government with no exception”. In this article, citizens have the right to legal protection. In connection with the rights, in Article 27 paragraph (1) mentioned above, citizens also have obligations, one of which is obliged to obey the law and government. In everyday life, despite the implementation of laws and regulations, there are often behaviors from the community and corporations that deviate or conflict with laws and regulations. In connection with trade activities that sell a product, there are still business actors who have not maintained the halalness of a product such as not obtaining a Halal Certificate, this is of course very detrimental to the community as consumers, various matters related to consumer protection issues have always been discussed by the community, especially the community as disadvantaged consumers. This research is a normative juridical legal research, the purpose of this research is to be able to produce legal arguments regarding the perspective of criminal law on products that have not been certified halal in Indonesia, as well as to find out the regulation of halal certification and halal labeling as a form of legitimacy of the halalness of a product and legal protection for consumers in Indonesia